Structural delineation of potent transmission-blocking epitope I on malaria antigen Pfs48/45 - Prasun Kundu (Nature Portfolio, 2018)
Malaria protein Pfs48/45 is a promising transmission-blocking antigen targeted by antibodies. Here, the authors determine the structure of its transmission-blocking epitope I, and generate a humanized monoclonal antibody that binds Pfs48/45 with high affinity.